Silencing of Apis mellifera dorsal genes reveals their role in expression of the antimicrobial peptide defensin‐1. Issue 5 (18th July 2018) - Lourenço, A. P.; Florecki, M. M.; Simões, Z. L. P.; Evans, J. D.
Abstract: Like all other insects, two key signalling pathways [Toll and immune deficiency (Imd)] regulate the induction of honey bee immune effectors that target microbial pathogens. Amongst these effectors are antimicrobial peptides (AMPs) that are presumed to be produced by the nuclear factors kappa B (NF‐κB) Dorsal and Relish from the Toll and Imd pathways, respectively. Using in silico analysis, we previously proposed that the honey bee AMP defensin‐1 was regulated by the Toll pathway, whereas hymenoptaecin was regulated by Imd and abaecin by both the Toll and Imd pathways. Here we use an RNA interference (RNAi) assay to determine the role of Dorsal in regulating abaecin and defensin‐1 . Honey bees have two dorsal genes ( dorsal‐1 and dorsal‐2 ) and two splicing isoforms of dorsal‐1 ( dorsal‐1A and dorsal‐1B ). Accordingly, we used both single and multiple (double or triple) isoform knockdown strategies to clarify the roles of dorsal proteins and their isoforms. Down‐regulation of defensin‐1 was observed for dorsal‐1A and dorsal‐2 knockdowns, but abaecin expression was not affected by dorsal RNAi. We conclude that defensin‐1 is regulated by Dorsal (Toll pathway).